Antibacterial composite nano material as well as preparation method and application thereof

By using modified mesoporous polydopamine coated with hyaluronic acid membrane in antibacterial materials and modifying gold on its surface to form composite nanomaterials, the problem that existing antibacterial materials are difficult to pass through the cell membrane is solved, effectively killing bacteria and fungi and significantly improving the antibacterial effect.

CN119522911APending Publication Date: 2025-02-28QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657591.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing antibacterial materials are difficult to pass through the cell membrane of bacteria or fungi, resulting in poor antibacterial effects.

Method used

Modified mesoporous polydopamine is coated with hyaluronic acid membrane and gold is modified on its surface to form a composite nanomaterial. The material absorbs light energy and converts it into heat under near-infrared light irradiation, activates BNN6 to release NO gas, destroys cell membranes, and inhibits microbial growth.

Benefits of technology

Effective killing of bacteria and fungi has been achieved, and the antibacterial effect has been significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522911A_ABST
    Figure CN119522911A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of antibacterial materials, and particularly relates to a composite nano material as well as a preparation method and application thereof. The composite nano material comprises modified mesoporous polydopamine coated with a hyaluronic acid membrane and gold modified on the surface of the hyaluronic acid membrane, the modified mesoporous polydopamine is prepared from copper ion chelated mesoporous polydopamine and BNN6 loaded on the copper ion chelated mesoporous polydopamine. Gold and mesoporous polydopamine in the composite nano material can absorb near-infrared light and convert the near-infrared light into heat under the irradiation of the near-infrared light, BNN6 is activated and can release NO gas harmful to fungi or bacteria along with temperature rise, and the NO gas can interfere the metabolic process of microorganisms, change the permeability of cell membranes, damage the cell membranes and inhibit the growth of the fungi or the bacteria, so that the growth of the fungi or the bacteria is inhibited. And even death is caused. According to the invention, NO gas and an inorganic antibacterial agent are jointly applied to microorganism resistance, and the antibacterial effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of antibacterial materials, and specifically relates to a composite nano material and a preparation method and application thereof. Background Art

[0002] In modern society, the ubiquitous pathogenic microorganisms have brought a constant threat to people's lives. In particular, the spread of pathogenic microorganisms such as Candida albicans, Escherichia coli, and Staphylococcus aureus has posed a major challenge to public health. In the face of these microorganisms that endanger human health, people are paying more and more attention to the development of materials with antibacterial or disinfectant effects. These studies are extremely important for protecting human health, reducing the occurrence of diseases, and creating a clean and healthy living environment.

[0003] The current antibacterial products mainly include silver ion coatings, zinc-based antibacterial agents, organic acid compounds, and some photodynamic antibacterial agents. These products inhibit the growth of microorganisms by releasing active ingredients or physical mechanisms. However, the current antibacterial materials still have shortcomings and are difficult to pass through the cell membranes of bacteria or fungi, resulting in poor antibacterial effects of antibacterial materials. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a composite nano material and a preparation method and application thereof. The composite nano material of the present invention can destroy the cell membrane of bacteria or fungi and has a good antibacterial effect.

[0005] The present invention provides a composite nanomaterial, comprising modified mesoporous polydopamine coated with a hyaluronic acid film, and gold modified on the surface of the hyaluronic acid film;

[0006] The modified mesoporous polydopamine includes copper ion chelated mesoporous polydopamine and BNN6 loaded on the copper ion chelated mesoporous polydopamine.

[0007] Preferably, the mass ratio of the hyaluronic acid membrane to the modified mesoporous polydopamine is 0.9-1.1:0.9-1.1.

[0008] Preferably, the mass ratio of the copper ion chelated mesoporous polydopamine to BNN6 is 0.9-1.1:0.9-1.1.

[0009] Preferably, the mass ratio of mesoporous polydopamine to copper ions in the copper ion chelated mesoporous polydopamine is 1:3-5.

[0010] The present invention also provides a method for preparing the composite nanomaterial described in the above technical solution, comprising the following steps:

[0011] Chelating mesoporous polydopamine with copper ions to obtain copper ion chelated mesoporous polydopamine;

[0012] The copper ion chelated mesoporous polydopamine is loaded with BNN6 to obtain modified mesoporous polydopamine;

[0013] The modified mesoporous polydopamine is coated with hyaluronic acid to obtain a hyaluronic acid film-coated modified mesoporous polydopamine;

[0014] The modified mesoporous polydopamine coated with the hyaluronic acid membrane is gold-modified to obtain the composite nanomaterial.

[0015] Preferably, the chelation comprises: first mixing the mesoporous polydopamine and a solution containing copper ions and stirring; the copper ions are provided by soluble copper salts, and the concentration of copper ions in the solution containing copper ions is 0.4-0.6 mol / L.

[0016] Preferably, the loading includes: mixing an aqueous solution of copper ion chelated mesoporous polydopamine and an ethanol solution of BNN6 and stirring for a second time; the concentration of the aqueous solution of copper ion chelated mesoporous polydopamine is 1.5-2.5 mg / mL, the concentration of the ethanol solution of BNN6 is 1.5-2.5 mg / mL, and the volume ratio of the aqueous solution of copper ion chelated mesoporous polydopamine and the ethanol solution of BNN6 is 0.9-1.1:0.9-1.1.

[0017] Preferably, the second stirring is performed at room temperature in the dark, and the second stirring time is 20 to 28 hours.

[0018] Preferably, the coating comprises: mixing the modified mesoporous polydopamine and hyaluronic acid solutions and stirring for a third time; the concentration of the hyaluronic acid solution is 0.9-1.1 mg / mL.

[0019] The present invention also provides the use of the composite nanomaterial described in the above technical solution or the composite nanomaterial obtained by the above preparation method in the preparation of antibacterial materials.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention provides a composite nanomaterial, comprising a modified mesoporous polydopamine coated with a hyaluronic acid film, and gold modified on the surface of the hyaluronic acid film; the modified mesoporous polydopamine comprises copper ion chelated mesoporous polydopamine and BNN6 loaded on the copper ion chelated mesoporous polydopamine. Under near-infrared light irradiation, the gold and mesoporous polydopamine in the composite nanomaterial can absorb near-infrared light and convert it into heat. As the temperature rises, BNN6 is activated to release NO gas that is harmful to fungi. NO gas can interfere with the metabolic process of microorganisms, change cell membrane permeability, destroy cell membranes, inhibit the growth of fungi or bacteria, and even cause death. The present invention combines NO gas and inorganic antibacterial agents for antimicrobial purposes, and has a good antibacterial effect. The present invention provides a new idea for antibacterial materials and has broad development prospects.

[0022] The data of the examples show that the composite nanomaterial of the present invention has good glutathione (GSH) consumption and NO release capabilities, and has a good killing effect on Candida albicans.

[0023] The present invention also provides a method for preparing the composite nanomaterial described in the above technical scheme, including chelating copper ions with mesoporous polydopamine, then loading BNN6 and encapsulating hyaluronic acid, and finally performing asymmetric gold modification; the composite nanomaterial prepared by the present invention can achieve effective killing of fungi or bacteria. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 Transmission electron microscope (TEM) images and scanning electron microscope (SEM) images, where (a) is the TEM image of MPDA, (b) is the TEM image of CMBH, and (c) is the TEM image of CMBHA; (d) is the SEM image of MPDA, (e) is the SEM image of CMBH, and (f) is the SEM image of CMBHA;

[0026] Figure 2 This is the TEM Mapping of CMBHA;

[0027] Figure 3 is the zeta potential of MPDA, CM, CMB, CMBH, and CMBHA;

[0028] Figure 4 Fourier transform infrared spectra of MPDA, CM, BNN6, CMB, HA, and CMBH;

[0029] Figure 5 is the UV-visible spectrum of the reaction between CMBHA and GSH at different concentrations after adding DTNB;

[0030] Figure 6 is the amount of NO released by CMBHA under 808nm light irradiation at different powers;

[0031] Figure 7 The antibacterial results of CMBHA, where (a) is the antibacterial plate photo of Candida albicans treated with different materials; (b) is the fungal survival rate of Candida albicans treated with different nanomaterials; (c) is the SEM image of Candida albicans after PBS and CMBHA+NIR treatment; scale bar: 2μm. DETAILED DESCRIPTION

[0032] The present invention provides a composite nanomaterial, comprising modified mesoporous polydopamine coated with a hyaluronic acid film, and gold modified on the surface of the hyaluronic acid film;

[0033] The modified mesoporous polydopamine includes copper ion chelated mesoporous polydopamine and BNN6 loaded on the copper ion chelated mesoporous polydopamine.

[0034] In the present invention, the mass ratio of the hyaluronic acid membrane to the modified mesoporous polydopamine is preferably 0.9-1.1:0.9-1.1, more preferably 1: 1. The present invention uses hyaluronic acid membrane to coat the modified mesoporous polydopamine, which can avoid the rapid release of copper ions and ensure that BNN6 does not fall off.

[0035] In the present invention, the mass ratio of the copper ion chelated mesoporous polydopamine to BNN6 is preferably 0.9-1.1:0.9-1.1, more preferably 1:1 。 The BNN6 (N,N'-di-sec-butyl-N,N'-dinitroso-1,4-phenylenediamine) can release NO gas which is harmful to fungi or bacteria.

[0036] In the present invention, the mass ratio of mesoporous polydopamine to copper ions in the copper ion chelated mesoporous polydopamine is preferably 1:3-5, more preferably 1:4; the ratio of mesoporous polydopamine to copper ions is preferably 200 mg:12.5 mmol. The copper ions are inorganic antibacterial agents.

[0037] In the present invention, the mesoporous polydopamine is preferably in a spherical structure, and the gold is preferably asymmetric gold.

[0038] The gold and mesoporous polydopamine are both photothermal conversion materials. Under the irradiation of near-infrared light, they can absorb near-infrared light and convert it into heat, thereby causing the temperature to rise and activating BNN6 to release NO that is harmful to fungi or bacteria.

[0039] The present invention also provides a method for preparing the composite nanomaterial described in the above technical solution, comprising the following steps:

[0040] Chelating mesoporous polydopamine with copper ions to obtain copper ion chelated mesoporous polydopamine;

[0041] The copper ion chelated mesoporous polydopamine is loaded with BNN6 to obtain modified mesoporous polydopamine;

[0042] The modified mesoporous polydopamine is coated with hyaluronic acid to obtain a hyaluronic acid film-coated modified mesoporous polydopamine;

[0043] The modified mesoporous polydopamine coated with the hyaluronic acid membrane is gold-modified to obtain the composite nanomaterial.

[0044] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.

[0045] The invention chelates mesoporous polydopamine with copper ions to obtain copper ion chelated mesoporous polydopamine (Cu-MPDA).

[0046] In the present invention, the mesoporous polydopamine is preferably prepared by a method comprising the following steps:

[0047] Firstly, polyether F127, 1,3,5-trimethylbenzene, water and ethanol are mixed to obtain an emulsion;

[0048] The emulsion, dopamine hydrochloride and alkaline solution are mixed for polymerization, and the solid-liquid separation is performed to obtain mesoporous polydopamine.

[0049] The dosage ratio of the polyether F127, 1,3,5-trimethylbenzene, water and ethanol is preferably 1.25g:500μL:25mL:25mL. The first mixing method is preferably ultrasound. The dosage ratio of the emulsion, dopamine hydrochloride and alkaline solution is preferably 50mL:375mg:2.25mL; the alkaline solution is preferably ammonia water, and the mass concentration of the ammonia water is preferably 25%. The polymerization is preferably carried out under stirring at room temperature, and the stirring time is preferably 2.5h. The solid-liquid separation method is preferably centrifugation, the speed of the centrifugation is preferably 12000rpm, and the time is preferably 20min. After the solid-liquid separation, it is preferably also included to wash and dry the obtained solid, the washing is preferably a mixed solution of water and ethanol, the volume ratio of water and ethanol in the mixed solution is preferably 1:1, and the number of washings is preferably 3 times; the drying is preferably freeze-drying, and the conditions of the freeze-drying preferably include: -80℃, 24h.

[0050] In the present invention, the dosage ratio of the mesoporous polydopamine to the copper ions is preferably 200 mg: 12.5 mmol. The dosage of the copper ions in the present invention provides a composite material with good antibacterial effect. Too much copper ions will cause pore blockage, thereby reducing the specific surface area of ​​the composite nanomaterial. Too little copper ions will result in poor release of copper ions, and the expected antibacterial effect cannot be achieved.

[0051] In the present invention, the chelation preferably includes: mixing mesoporous polydopamine and a solution containing copper ions and stirring them for the first time; the copper ions are preferably provided by soluble copper salts, and the soluble copper salts preferably include copper sulfate or copper chloride, and the concentration of copper ions in the solution containing copper ions is preferably 0.4-0.6 mol / L, more preferably 0.5 mol / L. The first stirring is preferably carried out at room temperature, and the room temperature is preferably 10-30°C, and the first stirring time is preferably 12h. After the chelation, it is preferably further included: solid-liquid separation, washing the obtained precipitate; the solid-liquid separation method is preferably centrifugation, and the washing reagent is preferably deionized water, and the number of times is preferably 3 times.

[0052] After obtaining the copper ion chelated mesoporous polydopamine, the present invention loads BNN6 (N,N'-di-sec-butyl-N,N'-dinitroso-1,4-phenylenediamine) on the copper ion chelated mesoporous polydopamine to obtain modified mesoporous polydopamine (Cu-MPDA-BNN6, i.e., copper ion chelated mesoporous polydopamine loaded with BNN6).

[0053] In the present invention, the BNN6 is preferably prepared by a method comprising the following steps:

[0054] Under a protective atmosphere, N,N-di-sec-butyl-p-phenylenediamine solution, ethanol, sodium nitrite solution and hydrochloric acid solution are mixed and stirred, and the solid-liquid separation is carried out to obtain BNN6.

[0055] The concentration of the N,N-di-sec-butyl-p-phenylenediamine solution is preferably 10mmol / L, the concentration of the sodium nitrite solution is preferably 6mol / L, the concentration of the hydrochloric acid solution is preferably 6mol / L, and the volume ratio of the N,N-di-sec-butyl-p-phenylenediamine solution, ethanol, sodium nitrite solution and hydrochloric acid solution is preferably 2.34:18:20:20. The stirring time is preferably 4 to 5h. The solid-liquid separation method is preferably centrifugation. After the solid-liquid separation, it is preferred that the obtained solid is washed and dried, and the washing is preferably carried out using a mixed solution of water and ethanol, and the volume ratio of water to ethanol in the mixed solution is preferably 1:1, and the number of washings is preferably 3 times; the drying is preferably freeze-drying.

[0056] In the present invention, the mass ratio of the copper ion chelated mesoporous polydopamine (Cu-MPDA) and BNN6 is preferably 1: 1. The amount of BNN6 used in the present invention provides a composite material with good antibacterial effect. Too little BNN6 releases less NO and has a poor antibacterial effect. As the amount of BNN6 increases, the loading amount of BNN6 increases accordingly. After reaching saturation, continuing to increase the amount of BNN6 will not significantly increase the loading amount.

[0057] In the present invention, the loading preferably includes: mixing an aqueous solution of copper ion chelated mesoporous polydopamine and an ethanol solution of BNN6 and stirring for the second time. The concentration of the aqueous solution of copper ion chelated mesoporous polydopamine is preferably 1.5-2.5 mg / mL, more preferably 2 mg / mL, the concentration of the ethanol solution of BNN6 is preferably 1.5-2.5 mg / mL, more preferably 2 mg / mL, and the volume ratio of the aqueous solution of copper ion chelated mesoporous polydopamine and the ethanol solution of BNN6 is preferably 0.9-1.1:0.9-1.1, more preferably 1:1. The second stirring is preferably carried out at room temperature and protected from light, and the second stirring time is preferably 20-28h, more preferably 24h. After the loading, it is preferably also included: solid-liquid separation, washing the obtained solid; the solid-liquid separation method is preferably centrifugation, the centrifugal speed is preferably 10000rpm, and the time is preferably 30min; the washing is preferably carried out with water, and the number of times is preferably 3 times.

[0058] After obtaining the modified mesoporous polydopamine (Cu-MPDA-BNN6), the present invention coats the modified mesoporous polydopamine with hyaluronic acid to obtain hyaluronic acid membrane-coated modified mesoporous polydopamine (Cu-MPDA-BNN6-HA, i.e., hyaluronic acid membrane-coated BNN6-loaded copper ion chelated mesoporous polydopamine).

[0059] In the present invention, the mass ratio of the modified mesoporous polydopamine to hyaluronic acid is preferably 1:1. 。 The amount of hyaluronic acid used in the present invention has a good coating effect and will not affect the release of copper ions and NO; too little hyaluronic acid cannot achieve the purpose of coating, while excessive hyaluronic acid will cause the coating layer to be too thick, affecting the release of copper ions and NO.

[0060] In the present invention, the coating preferably includes: mixing the solution of modified mesoporous polydopamine and hyaluronic acid and stirring for the third time. The concentration of the hyaluronic acid solution is preferably 0.9-1.1 mg / mL, more preferably 1 mg / mL. The third stirring is preferably carried out at room temperature, and the time of the third stirring is preferably 24 hours. After the coating, it is preferably further included: solid-liquid separation, washing the obtained solid; the method of solid-liquid separation is preferably centrifugation; the washing is preferably carried out with water, and the number of times is preferably 3 times.

[0061] After obtaining the modified mesoporous polydopamine (Cu-MPDA-BNN6-HA) coated with a hyaluronic acid membrane, the present invention performs gold modification on the modified mesoporous polydopamine coated with a hyaluronic acid membrane to obtain the composite nanomaterial.

[0062] In the present invention, the gold modification is preferably asymmetric gold modification, and the asymmetric gold modification preferably includes: dripping an ethanol solution of modified mesoporous polydopamine coated with a hyaluronic acid film on a wafer, spraying gold after drying, collecting the material on the wafer, and drying to obtain a composite nanomaterial. The concentration of the ethanol solution of modified mesoporous polydopamine coated with a hyaluronic acid film is preferably 1 mg / mL. The wafer is preferably a silicon dioxide wafer. The time of the gold spraying treatment is preferably 100s. The collection is preferably: immersing the wafer in ethanol for ultrasound, solid-liquid separation, and collecting the obtained solid. The present invention dries the nanomaterial on the wafer, sprays gold from above, and the part close to the wafer will not be sprayed, forming an asymmetric structure. The asymmetric gold structure, under the irradiation of 808nm light, will form thermophoresis to form a nanomotor, which can give it power so that the nanomaterial does not only stay on the surface of the Candida albicans group, but can penetrate into its interior.

[0063] The present invention also provides the use of the composite nanomaterial described in the above technical solution or the composite nanomaterial obtained by the above preparation method in the preparation of antibacterial materials.

[0064] In order to further illustrate the present invention, the composite nanomaterial provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0065] In the embodiments of the present invention, the materials and reagents used include:

[0066] Hyaluronic acid (HA), 1,3,5-trimethylbenzene (TMB), dopamine hydrochloride, copper sulfate, N,N-di-sec-butyl-p-phenylenediamine (BPA), and sodium nitrite (NaNO2) were purchased from Macklin. Polyether F127 was purchased from Sigma-Aldrich. Candida albicans (ATCC10231) was purchased from Guangdong Microbiological Culture Collection Center, and solid and liquid Sabouraud culture medium was purchased from Solarbio. Ammonia water and hydrochloric acid were purchased from Yantai Far East Fine Chemical Co., Ltd. Anhydrous ethanol was purchased from Sinopharm.

[0067] Instruments include:

[0068] The morphology of the materials was characterized by transmission electron microscopy (JEM2100 and FEI Talos F200x). Fourier transform infrared spectra were recorded using Thermo Scientific Nicolet iS20. Zeta particle size and potential measurements were performed at 25°C using a laser particle size analyzer (Zetasizer Nano ZS90). A thermal imager (FOTRIC 225S) was used to record the photothermal changes of the nanomaterials.

[0069] Example 1 Preparation of composite nanomaterials

[0070] 1. Synthesis of mesoporous polydopamine (MPDA)

[0071] In a 100 mL round-bottom flask, 1.25 g of polyether F-127, 500 μL TMB, 25 mL of deionized water, and 25 mL of anhydrous ethanol were added in sequence, and then ultrasonicated until the solution turned into a white emulsion. Next, 375 mg of dopamine hydrochloride and 2.25 mL of ammonia water (mass concentration 25%) were added to the white emulsion. , After stirring at room temperature for 2.5 h, the obtained mixture was centrifuged (12000 rpm, 20 min). Then, the precipitate was washed three times with a mixed solution of water and anhydrous ethanol in a volume ratio of 1:1. Finally, MPDA was obtained by freeze drying (freeze drying at -80 °C for 24 h).

[0072] 2. Synthesis of copper ion chelated mesoporous polydopamine (CM)

[0073] 200 mg of MPDA was added to 25 mL of 0.5 M CuSO4 solution and stirred at room temperature for 12 h. After stirring, the mixture was centrifuged and the precipitate was washed three times with deionized water to obtain CM.

[0074] 3. Synthesis of BNN6 (N,N'-di-sec-butyl-N,N'-dinitroso-1,4-phenylenediamine)

[0075] 2.34 mL of 10 mM N, N-di-sec-butyl-p-phenylenediamine aqueous solution was added to 18 mL of anhydrous ethanol and stirred under nitrogen protection. Next, 20 mL of 6 M sodium nitrite solution was slowly added, and after continuous stirring for 30 minutes, 20 mL of 6 M hydrochloric acid solution was added dropwise. It was observed that the color of the reaction solution changed from red to orange, and a beige precipitate was formed. After stirring for 4 hours, centrifugation was performed, and the precipitate was washed three times with a solution mixed with water and anhydrous ethanol in a volume ratio of 1: 1. Finally, BNN6 was obtained by freeze drying.

[0076] 4. Synthesis of modified mesoporous polydopamine (CMB, i.e., copper ion chelated mesoporous polydopamine loaded with BNN6)

[0077] 10 mg of CM was dissolved in 5 mL of deionized water, and 10 mg of BNN6 was dissolved in 5 mL of anhydrous ethanol. The two solutions were mixed and stirred for 24 h at room temperature and in the dark. After stirring, centrifugation was performed (10000 rpm, 30 min), and the precipitate was washed three times with deionized water to obtain CMB.

[0078] 5. Synthesis of hyaluronic acid membrane-coated modified mesoporous polydopamine (CMBH, i.e., hyaluronic acid membrane-coated BNN6-loaded copper ion chelated mesoporous polydopamine)

[0079] 10 mg of CMB was added to 10 mL of hyaluronic acid solution (concentration: 1 mg / mL), and then stirred at room temperature for 24 h. After stirring, centrifugation was performed, and then the precipitate was washed three times with deionized water to obtain CMBH.

[0080] 6. Synthesis of composite nanomaterials (CMBHA)

[0081] 1 mg of CMBH was dissolved in 1 mL of anhydrous ethanol, ultrasonically treated and centrifuged, and this process was repeated three times to clean the impurities in CMBH. After each cleaning, the old ethanol was discarded and new ethanol was added. Next, a 250 μL sample of the CMBH ethanol solution was dropped on a silica wafer and dried at room temperature. The dried silica wafer loaded with CMBH was gold-sprayed (99.99% gold target sputtered for 100 s). After the treatment, the silica wafer loaded with CMBH and gold was immersed in anhydrous ethanol and ultrasonically treated for 30 seconds to collect the material. The collected material was centrifuged, the anhydrous ethanol was poured out and replaced with 1 mL of deionized water, and dried to obtain CMBHA.

[0082] Test Example 1

[0083] 1. In vitro antibacterial test method

[0084] Candida albicans was used to test the antibacterial activity of different materials (including PBS, MPDA, CM, CMB, CMBH, and CMBHA). Candida albicans was cultured in liquid Sabouraud medium at 28°C and 180 rpm overnight until the logarithmic growth phase. Then, 100 μL of the logarithmic growth phase Candida albicans suspension (concentration of 10 8 CFU·mL -1) were mixed with different materials (PBS as solvent, 75 μg / mL) and incubated at room temperature for 4 hours. During this period, one group was irradiated with 808nm near-infrared light (NIR treatment), and the other group was not irradiated. Afterwards, the treated suspension was diluted 100 times, and 100 μL of the diluted suspension was evenly spread on Sabouraud agar plates and cultured at 28°C for 36 hours to evaluate the antibacterial effect of the nanoparticles.

[0085] 2. Results and Discussion

[0086] (1) Particle characterization

[0087] Figure 1 Transmission electron microscope (TEM) and scanning electron microscope (SEM) images of MPDA, CMBH and CMBHA are shown, and the scale bar in the figure is 100nm. Figure 1 (a) and (d) are TEM and SEM images of mesoporous polydopamine, respectively. These two images show that the synthesized mesoporous polydopamine has a spherical structure and obvious mesoporous characteristics. Figure 1 (b) and (e) are TEM and SEM images of CMBH, which show that CMBH also has a spherical structure and a hyaluronic acid outer membrane covering the surface can be observed. Figure 1 (c) and (f) show the TEM and SEM images of CMBHA, from which asymmetrically modified gold nanoparticles can be clearly seen.

[0088] Figure 2 The TEM Mapping image of CMBHA is shown, and the scale bar in the figure is 100nm. Figure 2 In the TEM Mapping element distribution map, copper elements and asymmetrically modified gold can be clearly observed.

[0089] Figure 3 The potential of MPDA is -24.3 mV. 2+ After chelation with MPDA, its potential changed to -6.5 mV. Subsequently, after loading BNN6, the potential of CMB further changed to -16.1 mV, which confirmed the successful loading of BNN6. The potential of CMBH was -32.6 mV, and this change was due to the encapsulation of HA. After asymmetrically modifying gold on CMBH, its potential changed to -21.1 mV, indicating the successful synthesis of the composite nanomaterial.

[0090] Figure 4 The Fourier transform infrared spectra of MPDA, CM, BNN6, CMB, HA, and CMBH. The characteristic peak of the infrared spectrum of BNN6 molecule is 1451cm -1A peak attributable to -NN=O stretching vibration can be observed around 1091cm -1 The peaks around 2800cm are the characteristic peaks of CN stretching vibration. -1 Near the CMB, the peak of CH stretching vibration can be identified. Compared with CM, the infrared spectrum of CMB also clearly shows the characteristic peak of BNN6, which indicates that BNN6 has been successfully loaded on CMB.

[0091] (2) Glutathione consumption and NO release

[0092] The DTNB test was used to examine the ability of nanomaterials to consume glutathione (GSH). Figure 5 From the data, it can be observed that with the increase of the concentration of the composite nanomaterial (the solvent is water), the UV-visible spectrum absorption peak at 412nm gradually decreases. This phenomenon indicates that with the increase of the concentration of the composite nanomaterial, the released Cu 2+ The concentration also increases, thereby enhancing the ability to consume GSH.

[0093] The ability of composite nanomaterials to release nitric oxide (NO) was investigated using the Bio-Tech NO detection kit. Figure 6 The amount of NO released by CMBHA under 808nm light irradiation of different powers. From the experimental data, it can be seen that as the 808nm laser power increases, the amount of NO released also increases. This is because the composite nanomaterial can absorb 808nm light energy and convert it into heat energy. The stronger the laser power, the more heat energy is converted, which increases the temperature of the NO precursor BNN6, thereby releasing more NO.

[0094] These two experimental results together show that the composite nanomaterial has excellent GSH consumption and NO release capabilities. GSH exists inside the fungi, and the composite nanomaterial has the ability to consume GSH, which can destroy the redox balance within the fungi, causing fungal lipid peroxidation and affecting fungal activity.

[0095] (3) Study on the antibacterial activity of CMBHA

[0096] The present invention studies the antibacterial effect of CMBHA nanomaterials on Candida albicans. Figure 7 (a) shows the photos of Candida albicans antibacterial plates treated with different materials; Figure 7 (b) shows the fungal survival rate of Candida albicans under the treatment of different nanomaterials; Figure 7 (c) shows the SEM images of Candida albicans after treatment with PBS and CMBHA+NIR; -NIR and +NIR represent no near-infrared light irradiation and near-infrared light irradiation, respectively. Figure 7As can be seen in (a) and (b), in the absence of 808nm light (NIR, power of 1W), MPDA has no obvious inhibition on the growth of Candida albicans, and under 808nm light irradiation, the antibacterial effect of MPDA is not very ideal. Similarly, the survival rate of Candida albicans under 808nm light conditions is about 20% compared with no light conditions, showing a stronger antibacterial effect, which may be due to photothermal stimulation and Cu 2+ The accelerated intake leads to the death of Candida albicans. CMB also shows better antibacterial effect under 808nm light conditions, and the survival rate of Candida albicans is about 7%. This is because CMB is converted into heat after absorbing 808nm light, prompting BNN6 to release NO, thereby killing Candida albicans. There was no significant difference in the antibacterial effect between the CMBH+NIR group and the CMB+NIR group, indicating that the encapsulation of hyaluronic acid does not affect its antibacterial properties. Compared with the CMBH+NIR group, CMBHA+NIR showed the best antibacterial effect, and the survival rate of Candida albicans was 0. This is because CMBHA can move after absorbing near-infrared light, continuously releasing copper ions and NO, and contacting more Candida albicans, thereby improving the antibacterial effect. In order to explore the effect of CMBHA+NIR treatment on the morphology of Candida albicans, the present invention used a scanning electron microscope (SEM) to observe the fungal morphology. According to Figure 7 In the results of (c), the fungal surface in the PBS control group was flat and the cell membrane remained intact; while in the CMBHA+NIR treatment group, the fungal morphology changed significantly, the integrity of the cell membrane was damaged, and severe collapse and folding occurred. These results indicate that CMBHA+NIR treatment damaged the cell membrane of Candida albicans, thereby affecting the activity of the fungus.

[0097] The present invention successfully synthesized a multifunctional nanomaterial CMBHA, which can activate the release of NO by absorbing near-infrared light and exhibits excellent ability to consume glutathione (GSH). CMBHA exhibits significant killing effect on fungi.

[0098] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A composite nanomaterial, characterized in that: It comprises a modified mesoporous polydopamine coated with a hyaluronic acid film, and gold modified on the surface of the hyaluronic acid film; The modified mesoporous polydopamine includes copper ion chelated mesoporous polydopamine and BNN6 loaded on the copper ion chelated mesoporous polydopamine.

2. The composite nanomaterial according to claim 1, characterized in that: The mass ratio of the hyaluronic acid membrane to the modified mesoporous polydopamine is 0.9-1.1:0.9-1.

1.

3. The composite nanomaterial according to claim 1, characterized in that: The mass ratio of the copper ion chelated mesoporous polydopamine to BNN6 is 0.9-1.1:0.9-1.

1.

4. The composite nanomaterial according to claim 1 or 3, characterized in that: The mass ratio of mesoporous polydopamine to copper ions in the copper ion chelated mesoporous polydopamine is 1:3-5.

5. The method for preparing the composite nanomaterial according to any one of claims 1 to 4, characterized in that: The following steps are involved: Chelating mesoporous polydopamine with copper ions to obtain copper ion chelated mesoporous polydopamine; The copper ion chelated mesoporous polydopamine is loaded with BNN6 to obtain modified mesoporous polydopamine; The modified mesoporous polydopamine is coated with hyaluronic acid to obtain a hyaluronic acid film-coated modified mesoporous polydopamine; The modified mesoporous polydopamine coated with the hyaluronic acid membrane is gold-modified to obtain the composite nanomaterial.

6. The preparation method according to claim 5, characterized in that: The chelation comprises: mixing mesoporous polydopamine and a solution containing copper ions and first stirring; the copper ions are provided by soluble copper salts, and the concentration of copper ions in the solution containing copper ions is 0.4-0.6 mol / L.

7. The preparation method according to claim 5, characterized in that: The loading includes: mixing an aqueous solution of copper ion chelated mesoporous polydopamine and an ethanol solution of BNN6 and stirring them for a second time; the concentration of the aqueous solution of copper ion chelated mesoporous polydopamine is 1.5-2.5 mg / mL, the concentration of the ethanol solution of BNN6 is 1.5-2.5 mg / mL, and the volume ratio of the aqueous solution of copper ion chelated mesoporous polydopamine and the ethanol solution of BNN6 is 0.9-1.1:0.9-1.

1.

8. The preparation method according to claim 7, characterized in that: The second stirring is performed at room temperature in the dark, and the second stirring time is 20 to 28 hours.

9. The preparation method according to claim 5, characterized in that: The coating comprises: mixing the modified mesoporous polydopamine and hyaluronic acid solution and stirring for a third time; the concentration of the hyaluronic acid solution is 0.9-1.1 mg / mL.

10. Use of the composite nanomaterial according to any one of claims 1 to 4 or the composite nanomaterial obtained by the preparation method according to any one of claims 5 to 9 in the preparation of antibacterial materials.